Factors Influencing the Efficacy of Anti-PD-1 Therapy in Chinese Patients with Advanced Melanoma. (26th September 2019) - Zhao, Lingdi; Yang, Yonghao; Ma, Baozhen; Li, Wei; Li, Tiepeng; Han, Lu; Zhang, Yong; Shang, Yi-Man; Lin, Hongwei; Gao, Quanli
Abstract : Purpose . Anti-PD-1 antibody improves the survival of patients with advanced melanoma. However, the efficacy and safety of anti-programmed death protein 1 (PD-1) antibody have not been fully elucidated in Chinese melanoma patients, who show high frequency of mucosal and acral melanoma subtypes; besides, the factors influencing the efficacy of anti-PD-1 antibody have not been evaluated broadly. Patients and Methods . Patients with advanced melanoma treated with regimens containing anti-PD-1 antibody from June 2016 to January 2019 were evaluated. Baseline characteristics and blood parameters were assessed, and outcome and adverse events were evaluated according to different regimens. The Cox proportional hazards regression model was used for univariate and multivariate analyses. Results . A total of 51 patients with advanced melanoma were included in this study. The overall objective response rate (ORR) was 17.6%, the disease control rate was 58.5%, and the median time to progression was 5.2 months. The ORR of patients with PD-1 blockade-based combination therapy, without liver metastases and higher level of C-reactive protein (CRP) before PD-1 blockade, is higher than that of those not. Univariate analysis based on clinical features showed that ECOG scores, liver metastasis, elevated lactate dehydrogenase (LDH), and CRP levels were the factors affecting time to progression (TTP). Multivariate analysis showed that elevated CRP before PD-1 blockade was an independent predictive factor for ORR of PD-1 blockade therapy (P = 0.009 ), while only Eastern Cooperative Oncology Group (ECOG) score was an independent predictor for TTP (P = 0.032 ). The treatment was well tolerated in these cohort patients, and there was no treatment-related death. Conclusion . Anti-PD-1 antibody-containing regimen was safe and effective in Chinese patients with advanced melanoma, and elevated CRP and ECOG score were independent factors predicting the efficacy of anti-PD-1 therapy.